Influence of Skeletal Muscle Mass and Spinal Alignment on Surgical Outcomes for Lumbar Spinal Stenosis - Eguchi, Yawara (Asian Spine J, 2018)
STUDY DESIGN: Retrospective observational study. PURPOSE: We considered the relationship between spinal alignment and skeletal muscle mass on clinical outcomes following a surgery for lumbar spinal stenosis (LSS). OVERVIEW OF LITERATURE: There are no reports of preoperative factors predicting residual low back pain following surgery for LSS. METHODS: Our target population included 34 women (mean age, 74.4 years) who underwent surgery for LSS. Prior to and 6 months after the surgery, systemic bone mineral density and lean soft tissue mass were measured using dual-energy X-ray absorptiometry. Skeletal muscle mass index (SMI) was calculated as the sum of the arm and leg lean mass in kilograms divided by height in meters squared. The spinal alignment was also measured. Clinical outcomes were evaluated using the Japanese Orthopedic Association scoring system, leg and low back pain Visual Analog Scale, and Roland–Morris Disability Questionnaire (RDQ). Additionally, we examined the bone mineral density, skeletal muscle mass, and spinal alignment before and after the surgery. We used the Spearman correlation coefficient to examine the associations among clinical outcomes, preoperative muscle mass, and spinal alignment. RESULTS: Sarcopenia (SMI <5.46) was observed in nine subjects (26.5%). Compared with normal subjects (SMI >6.12), RDQ was significantly higher in subjects with sarcopenia (p =0.04). RDQ was significantly negatively correlated with SMI (r =−0.42, p <0.05). There was a significant positive correlation between postoperative RDQ and pelvic tilt (PT; r =0.41, p <0.05). SMI and PT were significantly negatively correlated (r =−0.39, r <0.05). CONCLUSIONS: Good postoperative outcomes were negatively correlated with low preoperative appendicular muscle mass, suggesting that postoperative outcomes were inferior in cases of decreased appendicular muscle mass (sarcopenia). Posterior PT due to decreased limb muscle mass may contribute to postoperative back pain, showing that preoperatively reduced limb muscle mass and posterior PT are predictive factors in the persistence of postoperative low back pain.